Le harcèlement moral au travail : phénomène objectivable ou « concept horizon » ? - Daniel Faulx; Sophie Delvaux (Perspectives Interdisciplinaires sur le Travail et la Santé)
The aim of this paper is to carry out a semantic analysis of the definitions proposed in the scientific literature and in legal texts to describe workplace victimization phenomena. Starting with the observation that there is a great diversity in how these phenomena are considered, the authors attempted to identify recurrences and differences between these various definitions. Three semantic poles were identified: the consequences for people and the environment, hostile behaviours, and the resources of the parties in which various components could be studied. Two questions promoting debate also emerged: the necessity for the author’s intention to talk about a victimization situation, and the place of conflict in harassment processes. Analysis of these definitions led to critical reflection about the problem of evaluation, diagnosis and the intervention relating to such situations.